Ruang lingkup Ruang Lingkup Filsafat Ilmu: Hakikat Berpikir Filsafat, Tujuan, dan Landasan Filsafat Ilmu di Perguruan Tinggi - Al-Hakim Musthafa, Luqman; Adang Hambali (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
Science is an object of philosophical study with a broader scope of philosophical objects compared to science because science is only limited to empirical issues, while philosophy covers everything empirical and non-empirical. Therefore, the object of science in the study of philosophy is that which concerns empirical objects. Philosophy of science is a branch of philosophy that investigates and criticizes the basis, working methods, goals, and empowerment of science as a whole and the form of acquiring knowledge. Philosophy of science has the same characteristics of thinking as philosophy because philosophy of science is born from philosophical thought, these characteristics include: radical, systematic, comprehensive, coherent, and critical. The material object of philosophy of science is to discuss the facts and truths of all disciplines, confirmation, and logic used by all disciplines. While the formal object of philosophy of science is the philosophical study of facts and truths and the philosophical study of confirmation and logic. So the formal object of substantive facts includes and truth, while the formal object of instrumentality is confirmation and logic. Philosophy of Science has uniqueness in its respective views according to what is thought. The existence of humans is certainly increasingly advanced with the development of the era, so they must be able to have knowledge that can support future life, especially as academics who are required to be fundamental stakeholders in determining and finding the truth in life.